Wake interactions from a system of two cylinders subjected to forced excitation - Mahir, Necati (Lehigh University, 1993)
The structure of the wake between and downstream of a two-cylin- der system in tandem and side-by-side arrangements is investigated. The Reynolds number based on the cylinder diameter is 160. The control parameters are the excitation frequency and amplitude, as well as the phase angle between the oscillating cylinders Flow visualization using the hydrogen bubble technique and point velocity measurements via Laser Doppler anemometry allow characterization of the wake structure as a function of time. Irrespective of the cylinder arrangement, the wake structure exhibits a number of common features. When the cylinders are stationary, the wake exhibits random, intermittent switching between states of vortex formation. When the cylinder system is subjected to forced oscillation, the wake response generally exhibits increased organization A locked-in response, whereby the vortex formation is phase-locked to the motion of the cylinder system is attainable over a substantially wider range of excitation frequency than for the corresponding stationary cylinder. When the oscillation frequency is sufficiently close to the inherent vortex formation frequency of the two-cylinder system, the phase shift between the oscillating cylinders has an insignificant effect on the occurrence or non- occurrence of locked-in response, though the details of the vortex patterns are a function of phase shift. On the other hand, near the boundary of the locked in region of response, it is possible to manipulate the wake structure between locked-in and modulated states by variation of the phase shift between the oscillating cylinders. Finally, outside the region of locked-in response, it is possible to generate modulated, ordered patterns of response, whereby the wake pattern repeats at a multiple of the period of the cylinder oscillation. Each of these types of visualized response of the wake can be related to the spectrum of the velocity fluctuation in the wake. Locked-in response involves a sharp peak at the forcing frequency and its harmonics. On the other hand, modulated response involves coexistence of a number of peaks in the spectrum, each of which can be traced to the frequency of the oscillation cylinder, the inherent vortex formation frequency from the two-cylinder system, a modulation.
Sadece dijital ortamda erişilebilir.
Keywords: Dümen suyu (Akışkanlar dinamiği)